Resistance mechanisms in Pseudomonas aeruginosa - Rodríguez Rocha, Abad Edmundo (2024)
There is a growing interest in studying the various resistance mechanisms of Pseudomonas aeruginosa due to its high resistance to antibiotics, resulting in limited therapeutic options. The objective of this study is to provide a detailed description of the various resistance mechanisms of Pseudomonas aeruginosa, taking into account the structural and genetic characteristics of this bacterium. For this article, a literature review was conducted. The search was performed using the keywords "Pseudomonas aeruginosa," "Bacterial genes," "Bacterial proteins," and "Resistance of Pseudomonas aeruginosa." Twenty-five articles were identifed, of which 21 met the inclusion criteria. Pseudomonas aeruginosa exhibits several resistance mechanisms determined both genetically and structurally. These various mechanisms were classifed as intrinsic, acquired, and adaptive. The intrinsic mechanisms are the natural antimicrobial resistance of the bacterium. The acquired mechanisms are those that the bacterium can develop through mutations in its own genes or through the horizontal acquisition of mobilegenetic elements. The adaptive mechanisms are those that the bacterium develops to adapt to environmental circumstances. It is evident that Pseudomonas aeruginosa is a high-risk bacterium due to its high resistance, limited therapy options, and its ability to cause highly dangerous infections in humans.